2019
DOI: 10.1002/jcp.28183
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/chitosan hydrogel containing olfactory ectomesenchymal stem cells for sciatic nerve tissue engineering

Abstract: Regeneration and functional recovery after peripheral nerve damage still remain a significant clinical problem. In this study, alginate/chitosan (alg/chit) hydrogel was used for the transplantation of olfactory ectomesenchymal stem cells (OE‐MSCs) to promote peripheral nerve regeneration. The OE‐MSCs were isolated from olfactory mucosa biopsies and evaluated by different cell surface markers and differentiation capacity. After creating sciatic nerve injury in a rat model, OE‐MSCs were transplanted to the injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 52 publications
1
58
0
1
Order By: Relevance
“…In the past years, various kinds of scaffolds, such as hydrogels, nanofibers and decellularized matrices have been developed for tissue regeneration application [13,14]. Hydrogels provide a suitable porous and interconnected structure for tissue https://doi.org/10.1016/j.msec.2019.03.068 regeneration, mimicking the hydrated state of extracellular matrix [15,16]. Among possible hydrogels to be developed for tissue regeneration applications, conducting polymers are an efficient tool to control cellular behavior due to their electrical conductivity, which makes them good candidates in neural tissue engineering applications [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, various kinds of scaffolds, such as hydrogels, nanofibers and decellularized matrices have been developed for tissue regeneration application [13,14]. Hydrogels provide a suitable porous and interconnected structure for tissue https://doi.org/10.1016/j.msec.2019.03.068 regeneration, mimicking the hydrated state of extracellular matrix [15,16]. Among possible hydrogels to be developed for tissue regeneration applications, conducting polymers are an efficient tool to control cellular behavior due to their electrical conductivity, which makes them good candidates in neural tissue engineering applications [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Different ways of associating alginate and chitosan have been de scribed in the literature: by mixing at room (Florczyk et al, 2011;Xu et al, 2019;Lv et al, 2019) or higher temperature (Fletcher et al, 2017), bilayer (Banerjee and Ganguly, 2019) or layer by layer (Silva et al, 2017) assemblies, crosslinking (Baysal et al, 2016;Naghizadeha et al, 2018, Zhang et al, 2018, 3D printing (Liu et al, 2018), … They lead to biocompatible buildings whose mechanical properties can be variable (Francis et al, 2013;Salehi et al, 2019;Lv et al, 2019;Xu et al, 2019), even up to correspond to the mechanical properties of hard tissues Florczyk et al, 2013). In this context our strategy was to let these biopolymers chemically unmodified, in order to maintain their excellent initial biocompatibility, and to work on the process to obtain a macroporous 3D architecture with improved rheo logical properties compared with reference polymers.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, recent studies indicated that autophagy has an important role in the modulation of tumor stage and neurodegenerative disorders. Despite a great deal of investigation already in the field neurodegenerative disorders, there has recently been a marked increase in research in this area [214,215,216,217,218,219,220]. Among the main challenges in drug delivery are drug non-selective biodistribution, hydrophilicity, and cell uptake.…”
Section: Nanostructures For Autophagy Modulator Delivery Systemsmentioning
confidence: 99%